An Adult Cohort Success Model Proposal: From Crying Shame Governance toward Collaborative Community - Soni Simpson; Wendy Yanow; Tania Giordani (Adult Education Research Conference, 2014)
This exploratory study compares governance efficacy in two adult graduate program cohorts to understand whether the introduction of skill development within the curriculum might be beneficial in learning to manage shared governance. A Cohort Governance Curriculum Model is introduced.